Phenomena of Domestic Violence Against Women and Divorce in 2020-2022 in Indonesia: An Islamic Perspective - Hasanudin, Hasanudin; Mukhlas, Oyo Sunaryo; Noradin, Muhammad Farhan Bin Mat; Solehudin, Ending; Jubaedah, Dedah (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
The phenomenon of domestic violence for women which leads to divorce has increased dramatically since 2020-2022. In fact, acts of domestic violence have never been justified in religious teachings. Therefore, this study aims to explore the phenomenon of domestic violence against women and divorce in 2020-2022 in Indonesia as well as Islamic views on both. This research uses a qualitative approach to the phenomenological method with data sources taken from reports on social media such as Youtube, Instagram, and Facebook about the phenomenon of domestic violence and divorce in 2020-2022. The research process is divided into three stages, namely the orientation stage, the reduction stage, and the selection stage. The results of this study reveal that: First, the phenomenon of domestic violence against women and leading to divorce has increased; in 2020 there were 226,062 cases increasing to 349,635 cases in 2022. From the search results, cases of domestic violence were caused by several factors such as: 1) unstable family economy due to the pandemic situation spanning 2020-2022; 2) jealousy among spouses because of social media, 3) spouse's family interferes too much in household affairs, and; 3) early marriage; Second, Islamic syari'at through the Qur'an and Sunnah condemns acts of domestic violence in the household for any reason according to the demands of QS: 4: 21, QS: 4: 34, and HR. Bukhari No. 4942. The findings of this study indicate that married couples need to be given education on how to navigate the household ship before they get married so that it is not easy to do domestic violence between partners.